Exhausted parents in Japan: Preliminary validation of the Japanese version of the Parental Burnout Assessment. Issue 174 (7th October 2020) - Furutani, Kaichiro; Kawamoto, Taishi; Alimardani, Maryam; Nakashima, Ken'ichiro
Abstract: We examined the factorial structure and validity of a Japanese version of the Parental Burnout Assessment, the PBA‐J, with 1, 500 Japanese parents. The Parental Burnout Assessment measures burnout using four dimensions: exhaustion in one's parental role, contrast in parental self, feelings of being fed up, and emotional distancing. Confirmatory factor analysis on the PBA‐J supported a four‐factor model. Multiple‐group structural equation modeling with parent participants was supported for the factor‐loading invariance model. Mothers had higher parental burnout scores than fathers. We found moderate‐to‐strong correlation coefficients between the PBA‐J and the Parental Burnout Inventory (PBI‐J; the comparative burnout measure), and weak‐to‐moderate correlation coefficients between the PBA‐J and job burnout, neuroticism, co‐parenting disagreement, and family disorganization. The PBA‐J was correlated with parental perfectionism, particularly with concern over mistakes rather than sociodemographic variables. Overall, our findings provide initial evidence for the validity of the PBA‐J.